2019
DOI: 10.1097/jpn.0000000000000375
|View full text |Cite
|
Sign up to set email alerts
|

Through the Microbial Looking Glass: Premature Labor, Preeclampsia, and Gestational Diabetes

Abstract: The influence of microbial factors on adverse perinatal outcomes has become the focal point of recent investigations, with particular interest in the role of the microbiome and probiotic interventions. The purpose of this scoping review was to identify and critique the most recent evidence about these factors as they relate to pregnancies complicated by preeclampsia (PEC), preterm birth (PTB), and gestational diabetes mellitus (GDM). Four databases (PubMed, EMBASE, Web of Science, and Cochrane) were searched f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 96 publications
1
10
0
2
Order By: Relevance
“…Numerous studies support the involvement of human microbiota and microbial translocation in preeclampsia (PE) (140)(141)(142)(143). A meta-analysis of epidemiologic studies indicated that any viral or bacterial infection relates to a higher risk of PE (two-fold) (91).…”
Section: Gut Kidney Microbiome Axis and Pregnancy-related Complicationsmentioning
confidence: 99%
“…Numerous studies support the involvement of human microbiota and microbial translocation in preeclampsia (PE) (140)(141)(142)(143). A meta-analysis of epidemiologic studies indicated that any viral or bacterial infection relates to a higher risk of PE (two-fold) (91).…”
Section: Gut Kidney Microbiome Axis and Pregnancy-related Complicationsmentioning
confidence: 99%
“…Further, Li Juan et al demonstrated that preeclampsia is associated with a disrupted gut microbiota composition compared with that of women who had uncomplicated pregnancies (171). In a recent review of the current knowledge about the possible association between the microbiome and the development of preeclampsia, Dunn et al did a comprehensive literature search and reported that overall, five groups of investigators studied the microbiome of PEC (172). In two of the studies, the placenta site was analyzed; in the remaining three, the mouth, gut, or an intra-amniotic site was examined.…”
Section: Hypothesis For How Altered Microbiome Affects Pec and Iugrmentioning
confidence: 99%
“… 19 The presence of GDM, along with other risk factors such as high blood pressure and obesity during pregnancy, can also lead to premature labor and delivery. 20 Therefore, the most direct adverse pregnancy outcome of GDM patients with poor blood glucose and weight control is macrosomia, which will lead to a series of other adverse pregnancy outcomes. One study found that up to 12 hours of comprehensive nutritional care significantly reduces the incidence of macrosomia in patients with GDM.…”
Section: Discussionmentioning
confidence: 99%